Asymmetric sequential Au(i)/chiral tertiary amine catalysis: an enone-formation/cyanosilylation sequence to synthesize optically active 3-alkenyloxindoles from diazooxindoles. Issue 20 (15th February 2016) - Zhao, Yu-Lei; Cao, Zhong-Yan; Zeng, Xing-Ping; Shi, Jia-Meng; Yu, Yi-Hua; Zhou, Jian
Abstract : A gold-catalyzed enone-formation and asymmetric cyanosilylation sequence is developed, providing enantioenriched 3-alkenyloxindoles from diazooxindoles, furans and trimethylsilyl cyanide (TMSCN). Abstract : An unprecedented sequential gold-catalyzed enone-formation and bifunctional tertiary amine mediated asymmetric cyanosilylation reaction is developed, allowing the highly enantioselective synthesis of 3-alkenyloxindoles from diazooxindoles, furans and trimethylsilyl cyanide (TMSCN).